SOURCES OF PRODUCTION OF REACTIVE OXYGEN AND NITROGEN SPECIES IN TISSUES OF PERIODONTIUM AND SALIVARY GLANDS OF RATS UNDER MODELED SYSTEMIC INFLAMMATION - A.M. Yelins’ka; O.O. Shvaykovs’ka; V.O. Kostenko (Проблеми екології та медицини)
The purpose of the work was to reveal the sources of production of reactive oxygen and nitrogen species in the tissues of periodontium and salivary glands of rats under conditions of experimental systemic inflammation. The study was carried out on 20 white male rats of the Wistar line weighing 180-220 g, divided into 2 groups: the 1st included intact animals, the 2nd was made up of the animals with induced systemic inflammation. Systemic inflammation was induced by intraperitoneal administration of lipopolysaccharide Salmonella typhi (Pyrogenalum) in a dose that stimulated rise in temperature by 1.5 °C according to the scheme: during the first week, 4 minimum pyrogenic doses (MPD) of 0.4 μg/kg of rat mass were administered 3 times a week. During the following seven weeks of the experiment, rats were given 4 MPD / kg of body weight once a week. The research was guided by the principles of biomedical ethics. The animals were decapitated with ethereal anesthesia. Soft tissues of periodontium and submandibular salivary glands were the objects of the study. It has been found out that systemic inflammation is accompanied by an increase in the production of superoxide anion radical in periodontium tissues and salivary glands by mitochondrial and NADPH-dependent electron transport chains of microsomes and NO synthase as well as by leukocyte NADPH oxidase. We have revealed interfering with the mechanism of autoregulation of the physiological NO concentration in the tissues of periodontium and submandibular salivary glands that leads to simultaneous increase in NO formation through the NO-synthase and nitrate / nitrite reductase mechanisms, resulting in the development of oxidative-nitrosative stress with rising peroxynitrite concentration. We have also found out NOS uncoupling in the tissues of periodontium and salivary glands that is an additional source of superoxide anion radical as a leading factor in oxidative-nitrosative stress.